2017
DOI: 10.21206/rbas.v7i1.375
|View full text |Cite
|
Sign up to set email alerts
|

Extratos Vegetais, Formulações a Base De Extrato Vegetal E Produtos Químicos No Controle Da Mancha Bacteriana Do Maracujazeiro

Abstract: RESUMO -A mancha bacteriana é uma importante doença na cultura do maracujazeiro, responsável por perdas econômicas e pela redução da frutificação e do período de exploração comercial das plantas afetadas. O presente trabalho teve como objetivo avaliar o efeito dos produtos químicos oxitetraciclina, fluazinam, mancozeb, oxicloreto de cobre e Acibenzolar-S-Metil (ASM), das formulações Fitoforce Cobre, Fitoforce Plus e dos extratos de folhas de Artocarpus heterophyllus e Morinda citrifolia sobre o crescimento in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The use of formulations based on plant extracts (which have bioactive substances capable of acting as resistance inducers) has been subject to intense research (Costa et al, 2017). Guimarães et al (2016) verified that the application of Greenforce CuCa (formulation based on the by-products of the coffee industry supplemented with copper and calcium) and acibenzolar-S-methyl (ASM) reduced the incidence of BYS by 38% and 35%, respectively.…”
mentioning
confidence: 99%
“…The use of formulations based on plant extracts (which have bioactive substances capable of acting as resistance inducers) has been subject to intense research (Costa et al, 2017). Guimarães et al (2016) verified that the application of Greenforce CuCa (formulation based on the by-products of the coffee industry supplemented with copper and calcium) and acibenzolar-S-methyl (ASM) reduced the incidence of BYS by 38% and 35%, respectively.…”
mentioning
confidence: 99%
“…The highest mean observed was for the control treatment, with levels of 7.48 % of severity. Costa et al (2017) evaluated the effects of chemical products on the severity of bacterial leaf spot in passion fruit and showed that treatments with copper oxychloride limit the number of colonyforming units of Xanthomonas axonopodis pv. Passiflorae.…”
Section: Resultsmentioning
confidence: 99%
“…After 24 h of incubation at 30 • C, each plate was evaluated in terms of its inhibition halo (disk diffusion (Hamal et al, 2008) and expected reduced colony-forming units (CFU) in the plate diffusion (Costa et al, 2017). According to Santurio et al (2007), the present study considered "biocide concentration" once 100% mortality had occurred.…”
Section: Antibacterial Activitymentioning
confidence: 99%